A near-infrared fluorescent probe for monitoring leucine aminopeptidase in living cells. Issue 2 (8th November 2018) - Chai, Yun; Gao, Yuting; Xiong, Huiwen; Lv, Wanqian; Yang, Guichun; Lu, Cuifen; Nie, Junqi; Ma, Chao; Chen, Zuxing; Ren, Jun; Wang, Feiyi
Abstract : A novel water-soluble near-infrared fluorescent probe (CHMC-M-Leu) for specific monitoring of LAP in vitro and in vivo . Abstract : Leucine aminopeptidase (LAP), one of the important cancer-related biomarkers, is significantly over-expressed in many malignant tumor cells. Developing an effective fluorescent probe for high-specificity and in situ trapping of endogenous LAP in living samples is still challenging. In this project, we report a water-soluble near-infrared (NIR) fluorescent probe (CHMC-M-Leu) for specific monitoring of LAP in vitro and in vivo . The novel fluorescent probe (CHMC-M-Leu) contains a NIR-emitting fluorophore (CHMC-M) as the reporter andl -leucine as the enzyme-active trigger moiety which are linked together by a p -aminobenzyl alcohol (PABA) section. Upon exposure to LAP, the fluorescence at 625 nm gets impressively enhanced, which belongs to the near-infrared region and is beneficial for imaging in vivo . Furthermore, the novel fluorescent probe exhibits fast response and highly chemoselective detection of LAP in various bio-related species. In addition, CHMC-M-Leu shows favourable cellular uptake and was successfully used to monitor endogenous LAP in living cells.